2009
DOI: 10.1111/j.1468-3083.2008.03021.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the laboratory diagnosis of syphilis in East European countries

Abstract: The present guidelines aim to provide comprehensive and precise information regarding the laboratory diagnosis of the sexually transmitted infection (STI) syphilis in East European countries. These recommendations contain important information for laboratory staff working with STIs and/or STI-related issues. Individual East European countries may be required to make minor national adjustments to these guidelines as a result of lack of accessibility to some reagents or equipment, or laws in a specific country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
0
18
0
6
Order By: Relevance
“…En la etapa terciaria, no sólo se observa un bajo título de anticuerpos, sino además una baja carga infectante en el SNC, lo cual difi culta mucho el diagnóstico que, por lo tanto, se basa principalmente en las manifestaciones clínicas. Adicionalmente, se sabe que hay un alto número de falsos positivos en la serología asociados a diversas condiciones como embarazo, edad avanzada, mesenquimopatías y neoplasias 12 . Dado que no es posible cultivar esta bacteria, el diagnóstico de la enfermedad requiere métodos alternativos al cultivo [12][13][14] .…”
Section: Unidad De Infectología (Pvt)unclassified
See 2 more Smart Citations
“…En la etapa terciaria, no sólo se observa un bajo título de anticuerpos, sino además una baja carga infectante en el SNC, lo cual difi culta mucho el diagnóstico que, por lo tanto, se basa principalmente en las manifestaciones clínicas. Adicionalmente, se sabe que hay un alto número de falsos positivos en la serología asociados a diversas condiciones como embarazo, edad avanzada, mesenquimopatías y neoplasias 12 . Dado que no es posible cultivar esta bacteria, el diagnóstico de la enfermedad requiere métodos alternativos al cultivo [12][13][14] .…”
Section: Unidad De Infectología (Pvt)unclassified
“…Adicionalmente, se sabe que hay un alto número de falsos positivos en la serología asociados a diversas condiciones como embarazo, edad avanzada, mesenquimopatías y neoplasias 12 . Dado que no es posible cultivar esta bacteria, el diagnóstico de la enfermedad requiere métodos alternativos al cultivo [12][13][14] . El estándar de oro para la detección de T. pallidum es el test de "infectividad" en conejos (en inglés rabbit infectivity test -RIT), el cual requiere disponibilidad de animales y un tiempo prolongado de análisis, por lo que resulta impracticable en el laboratorio clínico 15,16 .…”
Section: Unidad De Infectología (Pvt)unclassified
See 1 more Smart Citation
“…The present guidelines were elaborated as a consensus document of the Eastern European Sexual and Reproductive Health Network 1 and comprise one element of a series of guidelines aimed at optimization, standard ization, and quality assurance of the laboratory diagnosis of the reproductive tract infections. [2][3][4] Chlamydia trachomatis is a major cause of genital tract infections among sexually active adolescents and young persons. 5 It has been reported that pelvic inflammatory disease may occur in £ 40% of women with untreated C. trachomatis genital tract infection 6,7 with a significant but uncertain number developing tubal factor infertility, ectopic pregnancy or chronic pelvic pain.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines were formulated by the network participants during previous meetings, using evidencebased principles. This approach stimulated direct communication between leading experts from "East" and "West", resulting in consensus documents which were first published internationally [6][7][8] and then subsequently adopted and published at the national level [1,2].…”
mentioning
confidence: 99%